2002
DOI: 10.1200/jco.2002.20.4.1094
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Residual Disease Tests Provide an Independent Predictor of Clinical Outcome in Adult Acute Lymphoblastic Leukemia

Abstract: The association of MRD test results and DFS was independent of and greater than other standard predictors of outcome and is therefore important in determining treatment for individual patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
99
2
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(112 citation statements)
references
References 34 publications
7
99
2
3
Order By: Relevance
“…As a matter of fact, this patient selection might have represented a factor interacting with the ASCT effect, as it appeared for instance that rapid rather than slow responders were those who could actually benefit from ASCT. This is reminiscent of results reported in studies evaluating the value of minimal residual disease (MRD) status in the context of ASCT, either in patients with ALL, 36 Ph-positive ALL, 37 or acute promyelocytic leukemia. 38 In all these studies, patients with a high MRD level a Defined as ALL which needed two induction courses for CR achievement and/or BCP-ALL with at least one of the following factors: (1) WBCX30 G/l; (2) CD10À; (3) high-risk cytogenetics.…”
Section: Discussionmentioning
confidence: 67%
“…As a matter of fact, this patient selection might have represented a factor interacting with the ASCT effect, as it appeared for instance that rapid rather than slow responders were those who could actually benefit from ASCT. This is reminiscent of results reported in studies evaluating the value of minimal residual disease (MRD) status in the context of ASCT, either in patients with ALL, 36 Ph-positive ALL, 37 or acute promyelocytic leukemia. 38 In all these studies, patients with a high MRD level a Defined as ALL which needed two induction courses for CR achievement and/or BCP-ALL with at least one of the following factors: (1) WBCX30 G/l; (2) CD10À; (3) high-risk cytogenetics.…”
Section: Discussionmentioning
confidence: 67%
“…[1][2][3][4][5][6][7][8][9][10][11][13][14][15] Although some of these studies demonstrated that MRD maintained prognostic significance in Cox-model multivariate analyses, these studies generally have not had enough patients to understand the relation between MRD and other risk factors, or to determine if there was any interaction among variables. That is, it is not clear if the prognostic significance of finding MRD is the same in all patient groups.…”
Section: Discussionmentioning
confidence: 99%
“…1,[5][6][7][8]13,14,26,[29][30][31][32] MRD has been studied at multiple time points throughout treatment. These studies show that although patients are noted to be positive less frequently as treatment progresses, MRD has prognostic significance at several time points.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[27][28][29]36,37,39,[42][43][44][47][48][49]53,54,57,[59][60][61] The association between MRD and risk of BM relapse is likely 'dose-dependent' in ALL 27,28,36,37,41,42,44,47,63 and, possibly, AML, 53,54,60 while MRD assessments may fail to predict extramedullary relapse accurately. 32,45 Interestingly, evidence from logistic regression models suggests that the relative level of MRD has more impact on survival in ALL than in AML. 47 Many open questions remain to be addressed in future studies.…”
Section: The Concept and Determination Of Mrdmentioning
confidence: 99%